The Correlation between the Level of Physical Activity and the Incidence of Breast Cancer in RSUD Dr. Soetomo Surabaya - Yovita Kristiani Widiyatno; Asdi Wihandono; Samsriyaningsih Handayani (Riviera Publishing, 2024)
Breast cancer is one of the most common cancers worldwide. This study aims to investigate and analyze the relationship between the level of physical activity and the occurrence of breast cancer at Dr. Soetomo Hospital Surabaya. The research method employed in this study is correlation analysis. The sample population was obtained from the Cancer Service Development Center (PPLK) at Dr. Soetomo Hospital Surabaya. The results of this study indicate that the majority of the 53 research subjects suffering from breast cancer had low-intensity physical activity since childhood to adolescence, with 41.5% of the total subjects (22 patients). In contrast, only 24.5% (13 patients) and 34% (18 patients) had moderate and high-intensity physical activity, respectively. Statistical analysis using Microsoft Excel version 2019 and SPSS showed that the calculated Chi-square value was greater than the tabulated Chi-square value, thus rejecting the null hypothesis (H0). This indicates a significant relationship between the intensity of physical activity during childhood to adolescence and the occurrence of breast cancer in the research subjects. This study implicates the importance of awareness regarding the significance of physical activity in maintaining breast health, especially from a young age. The practical implication of this research is the necessity of a preventive approach to breast cancer involving the promotion of a healthy lifestyle and regular physical activity, particularly during childhood and adolescence.